Implementasi Metode K-Means Sebagai Upaya Penentuan Lokasi Promosi Penerimaan Siswa Baru - Azmi, Nurul; Helmiah, Fauriatun; Sudarmin, Sudarmin (Building of Informatics, Technology and Science (BITS), 2022)
Smart Study Center is a computer course located in Kisaran City, Asahan Regency, North Sumatra Province. This computer-based course has promoted to various places, especially around Kisaran City. But sometimes there are obstacles in doing this, because it is not easy to determine the location of the promotion quickly and precisely. Promotion is the communication of information between sellers and potential buyers or others in the channel to influence attitudes and behavior. In addition, the application of information technology in the field of promotion can facilitate the management of information which, if processed properly, can produce new knowledge that is very useful in making future decisions. It takes research and consideration of many aspects which of course will take a lot of time. The majority of the Smart Study Center Kisaran students come from various public and private vocational high schools and high schools in Kisaran City and its surroundings. This is certainly one of the important factors to promote the acceptance of new students in an effort to increase the number of new students every year. With the application of data mining using the K-Means Clustering method on the acceptance of new students in the Smart Study Center Kisaran course by grouping research object items based on their similarity in nature, so that information will be obtained about which areas have high potential to bring in new students. K-Means Clustering can group large enough data quickly and accurately so that decision making in determining the location of the promotion in the next year can be done effectively and efficiently. The data attributes used in this study are the names of majors such as, TKJ, RPL, and Ms Office. The result of this system is the determination of the location of the promotion with 2 clusters i.e. feasible (C1) and unfit (C2)